The microbiological detection of Mycobacterium tuberculosis from oral lesion - Atik Kurniawati (Dental Journal (Majalah Kedokteran Gigi), 2007)
Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis. The oral manifestations of tuberculosis have been reported. The objectives of this study was to detect Mycobacterium tuberculosis from oral lesions by swabbing. Samples were received from collected primary data on annually clinical report status and then clinical intra oral examination was performed. Oral lesions were swabbed and cultured using Lowenstein Jensen media, Middlebrook 7H9 and Middlebrook 7H10. Positive culture were recorded and observed everyday until 8 weeks. From 66 samples, there were 2 patients with ulcer as an oral clinical manifestation with location on the tongue. Culture examination revealed 2 positive samples. It was inferred that Mycobacterium tuberculosis could be detected in oral lesion by swabbing.